Abiotic Changes Driving Microphytoplankton Functional Diversity in Admiralty Bay, King George Island (Antarctica) - Lima, Domênica Teixeira de; Moser, Gleyci Aparecida Oliveira; Piedras, Fernanda Reinhardt; Cunha, Leticia Cotrim da; Tenenbaum, Denise Rivera; Tenório, Márcio Murilo Barboza; Campos, Marcos Vinícius Pereira Borges de; Cornejo, Thais de Oliveira; Barrera-Alba, José Juan (Frontiers in Marine Science, 2019)
Environmental gradients can provide habitat-specific scenarios for community functional diversity that determine the composition of populations on both spatial and temporal scales. The western shelf of the Antarctic Peninsula has experiencing increasing air temperatures while the climate is transitioning to a warm-humid sub-Antarctic-type of climate. As a consequence, abiotic changes are leading to alterations in the trophic web. Microphytoplankton functional diversity was analyzed across environmental gradients of sea surface temperature, salinity, meltwater percentage and nutrient availability in Admiralty Bay, South Shetland Islands, Western Antarctic Peninsula. Samples were collected during the austral summer from 2009 to 2011 and from 2013 to 2015, at Admiralty Bay for which functional diversity indices were calculated based on species traits. The amount of meltwater (MW) present in Admiralty Bay groups microphytoplankton into communities according to physiological and ecological tolerances, thus leading to a greater functional diversity. When meltwater dominated the bay (> 2.25% MW scenarios iii - 2013-14 and iv - 2014-15), diatoms and dinoflagellates were codominant. An increase in the dinoflagellate fraction of microphytoplankton can be considered a trigger for changes in the structure of the Antarctic food web. Our results suggest using Admiralty Bay as a model for studies on changes in microphytoplankton community composition and functional diversity.